On the Labor Theory of Property: Is the Problem Distribution or Predistribution?. Issue 2 (4th March 2017) - Ellerman, David
Abstract : The value of the marginal productivity of labor is the usual basis for the ideal competitive distribution of pay to workers. But the prior question of predistribution is: "Who is to be the firm in the first place?" That question is addressed by the modern treatment of the labor or natural rights theory of property—which implies that the members of the firm should always be the people who work in it who would thereby jointly appropriate the positive and negative fruits of their labor.